The Impact of Attending Religious Schools on the Moral Competencies of Accounting Students - Umaru Mustapha Zubairu (Intelektual Pustaka Media Utama, 2016)
For over a century, scholars have argued that religious education is crucial for the developed of students' moral competencies. This study sought to empirically test this assertion by comparing the moral competencies of two sets of Muslim accounting students: those who had attended a religious secondary school and those who attended a public (secular) secondary school in Malaysia. The focus on accounting students is quite important in an era where the moral competencies of accountants has been in the public eye due to their complicity in the rash of financial scandals that have plagued the business world over the last two decades. The Muslim Accountant Moral Competency Test (MAMOC) was developed by a collaboration with Islamic accounting scholars and was used to measure the students' moral competencies. Although the results revealed that there was no difference in the moral competencies of both sets of students, they both displayed satisfactory levels of moral competency which vindicates the Malaysian government's policy of mandating Islamic education in all secondary schools, whether religious or secular.